The Relationship Between Students' Self-Confidence and Their Motivation to Speak English (An Investigation at 11th Grade Students at MA Banat Thohir Yasin) - Kamilia, Kamilia; Prasetyaningrum, Ari; Arfah, Hajriana; Usuluddin , Usuluddin (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
This study aimed to find out wheter there was any correlation between students’ self-confidence and their motivation to speak English. This research methode was quantitative with the correlational research design. The research took 20 students of the eleventh-grade students at MA Banat Thohir Yasin as the sample. The instruments used to collect the data were questionnaire and speaking test. The questionnaire to assess students’ self-confidence and motivation, while speaking test to assess students in speaking English. To analyze the data, the researcher used correlations Pearson Product Moment to find out the correlation between students’ self-confidence and their motivation to speak English. The research used SPSS 25 programs as the statistical program to analyze the data. The data found that (1) there was correlation between students’ self-confidence and speaking with the signifcant value was 0.001 < 0.005 and the correlation coefficient r = 0.666. (2) there was correlation between students’ motivation and speaking with the significant value was 0.000 < 0.005 and the correlation coefficient r = 0.904. From the result of the research, it can be concluded that there was a significant correlation between self-confidence and their motivation to speak English.